Workforce Development and Job Gratification of Support Workers in Selected Institutions in Lagos, State Nigeria - Majekodunmi, Samuel Ayodele; Olajide-Arise, Temi (Acta Universitatis Danubius. Œconomica, 2024)
Enquiries on workforce development and job gratification remain limited in Nigeria. More so, in connection with the plight of support workers in selected higher institutions of learning in Lagos State, Nigeria. The scenario has lingered for too long; consequently, there is scarcity of reports on ways to address obsolete skill, which has created consistent nervousness among support workers in tertiary institutions in Lagos State, Nigeria. The need to discontinue the trend and close the gap has motivated this enquiry. The study embraced survey research design, 4800 support workers constituted the study population. Using Krecjie and Morgan’s (1970) Table, the study obtained a sample of three hundred and fifty-seven (357), same figure corresponds to number of participants, who responded to copies of questionnaire administered. Using SPSS Version 26, the study achieved data analysis. Findings derived from analysis indicated that workforce development has an insignificant effect on job gratification of support workers in selected institutions in Lagos State, Nigeria. The conclusion is that workforce development generates job gratification among support staff in selected institutions in Lagos State, Nigeria. The study recommends that management of the universities need to rejig their extant policy to nip in bud, all competency-related anxieties.